Antagonistic Mechanism of Metabolites Produced by Lactobacillus casei on Lysis of Enterohemorrhagic Escherichia coli - Aditya, Arpita; Peng, Mengfei; Young, Alana; Biswas, Debabrata (Frontiers in Microbiology, 2020)
Enhancing extracellular metabolic byproducts of probiotics is one of the promising strategies to improve overall host health as well as to control enteric infections caused by various foodborne pathogens. However, the underlying mechanism of action of those metabolites and their effective concentrations are yet to be established. In this study, we determined the antibacterial potential of the metabolites in the cell-free culture supernatant (CFCS) collected from wild-type Lactobacillus casei (LCwt) and genetically modified LC to overexpress linoleate isomerase (LCCLA). We also evaluated the mechanism of action of CFCSs collected from the culture of LCwt in the presence or absence of 0.5% peanut flour (CFCSwt and CFCSwt+PF, respectively) and LCCLA alone (CFCSCLA) against enterohemorrhagic Escherichia coli (EHEC). The metabolites present in CFCSwt+PF and CFCSCLA eliminated EHEC within 24 and 48 h, respectively. Whereas CFCSwt failed to eliminate EHEC but reduced their growth by 6.7 logs (p < 0.05) as compared to the control. Significant downregulation of the expression of cell division gene, ftsZ, supported the observed degree of bactericidal and bacteriostatic properties of the collected CFCSs. Upregulation of EHEC genes related to maintaining cell membrane integrity, DNA damage repair, and molecular chaperons indicated an intensive stress condition imposed by the total metabolites present in CFCSs on EHEC growth and cellular structures. A range of deviated morphological features provoked by the metabolites indicated a membrane-targeted action, in general, to compromise the membrane permeability of EHEC. The information obtained from this study may contribute to a more efficient prevention of EHEC related infections.